Theology of Christian education on leading toward spiritual transformation in the frame of religious moderation in digital society context - Marpaung, Agus Marulitua; Hwang, Byung June (KURIOS, 2023)
Christian education is being challenged by the transformation of culture in a digital society and some problems that still occur due to religious diversity in Indonesia, such as intolerance, discrimination, and radicalism. Religious moderation is one of the priority programs of The Ministry of Religion Republic of Indonesia to achieve harmony and peace in society. Therefore, this research aims to explore the Theological study of Christian education in leading toward spiritual transformation based on religious moderation in a digital society. Using a qualitative research methodology with a Library-research approach, this study explored studies and literature reviews on the Theology of Christian education, spiritual transformation, and religious moderation. Based on the results of the data analysis in the literature review, This research formulates spiritual transformation in the frame of Religious moderation, such as transforming into a righteous life, loving life, and good citizenship.